2018
DOI: 10.1373/jalm.2017.023911
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Utility of High-Sensitivity Dried Blood Spot Immunoassay Testing with Single Molecule Counting

Abstract: Background: Dried blood spot (DBS) testing has been used for years in newborn screening and for other applications when obtaining blood by venipuncture is impractical or expensive. However, several technical challenges have restricted the use of DBS testing to qualitative assays or to analytes that are present in relatively high concentrations. The application of high-sensitivity detection using single molecule counting (SMC™) technology can potentially overcome the limitations of DBS as specimen source. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…We suggest that future assay methods involve the scanning and calculation of DBS surface area and blood volume calculated as a quality control step when the hematocrit is known or calculated in clinical studies for the measurement of different drugs. Another study by Mukherjee et al used the ImageJ ® software to find the correlation between surface area and blood volume,25 however, in our study we found the correlation between blood volume, surface area, and hematocrit level all together in one model makes the prediction of either HCT or BV easier.Variation in hematocrit levels between patients and inaccuraciesin blood volumes applied to Guthrie cards can have a marked effect on analyte concentrations measured in DBS samples. The current…”
contrasting
confidence: 77%
See 1 more Smart Citation
“…We suggest that future assay methods involve the scanning and calculation of DBS surface area and blood volume calculated as a quality control step when the hematocrit is known or calculated in clinical studies for the measurement of different drugs. Another study by Mukherjee et al used the ImageJ ® software to find the correlation between surface area and blood volume,25 however, in our study we found the correlation between blood volume, surface area, and hematocrit level all together in one model makes the prediction of either HCT or BV easier.Variation in hematocrit levels between patients and inaccuraciesin blood volumes applied to Guthrie cards can have a marked effect on analyte concentrations measured in DBS samples. The current…”
contrasting
confidence: 77%
“…Blank blood from healthy volunteers was collected in the EDTA tubes then centrifuged, separated and accurate amounts of red blood cells and plasma were mixed to obtain blood samples of different hematocrit (HCT) levels (25,30,35,40,45, 50, and 55%), This range was selected to cover the HCT levels expected in patients. Aliquots Health, USA).…”
Section: Methodsmentioning
confidence: 99%
“…However, recent efforts do suggest the applicability towards larger biomolecules177,178 . Some investigations has also utilized DBS and DMS for proteomic investigations as concept studies87,[179][180][181][182] . Nevertheless, DMS and DBS are not extensively reported for analysis of low abundance biomarkers.…”
mentioning
confidence: 99%
“…However, rapid serum point-of-care tests are not yet accessible in routine clinical practice. [32][33][34] Here, we review the current state, pragmatic considerations, and future implications of point-of-care testing and home testing for noninvasive IBD monitoring in the tight control model.…”
mentioning
confidence: 99%